2023
DOI: 10.1038/s41598-023-29258-9
|View full text |Cite
|
Sign up to set email alerts
|

Yoghurt as a deglutition aid for oral medication: effects on famotidine powder dissolution rate and pharmacokinetics

Abstract: Deglutition aid foods are used to help patients with dysphagia take oral medications. Yoghurt is occasionally used to help swallow medications; however, its influence on pharmacokinetics is poorly understood. Yoghurt made with Lactococcus cremoris subsp. cremoris FC has a characteristic viscous texture that facilitates bolus formation and deglutition due to its metabolite exopolysaccharide. We assessed yoghurt prepared with L. cremoris FC as a food deglutition aid. We performed a dissolution test using famotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Ilgaz et al [ 29 ] found that in rabbits regardless of thickness level, administration of levetiracetam with thickening agents does not affect the bioavailability of the drug. Gotoh et al [ 30 ] compared the administration of famotidine without food, with yoghurt and with thickener in rats. They found no difference in plasma concentrations in all 3 groups (with levels being taken up to 6 h after administration).…”
Section: Discussionmentioning
confidence: 99%
“…Ilgaz et al [ 29 ] found that in rabbits regardless of thickness level, administration of levetiracetam with thickening agents does not affect the bioavailability of the drug. Gotoh et al [ 30 ] compared the administration of famotidine without food, with yoghurt and with thickener in rats. They found no difference in plasma concentrations in all 3 groups (with levels being taken up to 6 h after administration).…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the immersion time of tablets in thickened solution was found effective to prevent the non-disintegration 353) . Yogurt made with L. cremoris FC was found to be useful as a deglutition aid for tablets 354,355) .…”
Section: Texture Design Of Food For Dysphagiamentioning
confidence: 99%